Activation of protein kinase p70S6K1 in peripheral blood mononuclear cells of patients with cancer and diabetes - Vatseba, T.S.; Sokolova, L.K.; Pushkarev, V.V.; Kovzun, O.I.; Pushkarev, V.M.; Tronko, M.D. (Reports of the National Academy of Sciences of Ukraine, 2019)
The IRS/PI3K/Akt/mTOR/p70S6K signaling cascade controls the cell growth and homeostasis in response to environmental signals such as levels of amino acids, glucose, energy, oxygen, and action of growth factors. The final link of this cascade is protein kinase p70S6K, which controls the protein synthesis, ribosomal biogenesis, cell cycle, apoptosis, splicing of mRNA, and other important processes. Disturbance of the IRS/PI3K/Akt/mTOR/ p70S6K cascade regulation can lead to serious diseases such as cancer, obesity and type 2 diabetes with complications. We study the activation of p70S6K1 in peripheral mononuclear blood cells (PMBC) of patients with cancer and diabetes by immunoenzyme analysis. It has been shown that, in PMBC patients with cancer and diabetes, the phosphorylation of p70S6K1 (Thr389) increases, indicating the activation of a kinase, which plays an important role in the formation of insulin resistance and tumor progression. Perhaps, this is due to elevated levels of insulin and IGF-1 in blood of these groups. However, in cancer patients with diabetes, the phosphorylation of p70S6K1 and, accordingly, its activity are significantly reduced compared with groups of patients with cancer or diabetes. The mechanisms for such a decrease in p70S6K1 activation are discussed.